Fecal Microbial Transplant Capsules Are Safe in Hepatic Encephalopathy: A Phase 1, Randomized, Placebo‐Controlled Trial. Issue 5 (18th June 2019) - Bajaj, Jasmohan S.; Salzman, Nita H.; Acharya, Chathur; Sterling, Richard K.; White, Melanie B.; Gavis, Edith A.; Fagan, Andrew; Hayward, Michael; Holtz, Mary L.; Matherly, Scott; Lee, Hannah; Osman, Majdi; et al.
Abstract : Hepatic encephalopathy (HE) can cause major morbidity despite standard of care (SOC; rifaximin/lactulose). Fecal microbial transplant (FMT) enemas postantibiotics are safe, but the effect of FMT without antibiotics using the capsular route requires investigation. The aim of this work was to determine the safety, tolerability, and impact on mucosal/stool microbiota and brain function in HE after capsular FMT in a randomized, single‐blind, placebo‐controlled clinical trial in Virginia. Patients with cirrhosis with recurrent HE with MELD (Model for End‐Stage Liver Disease) <17 on SOC were randomized 1:1 into receiving 15 FMT capsules versus placebo from a single donor enriched in Lachnospiraceae and Ruminococcaceae. Endoscopies with duodenal and sigmoid biopsies, stool analysis, cognition, serum lipopolysaccharide‐binding protein (LBP), and duodenal antimicrobial peptide (AMP) expression at baseline were used. Clinical follow‐up with SOC maintenance was performed until 5 months. FMT‐assigned patients underwent repeat endoscopies 4 weeks postenrollment. Twenty subjects on lactulose/rifaximin were randomized 1:1. MELD score was similar at baseline (9.6 vs. 10.2) and study end (10.2 vs. 10.5). Six patients in the placebo group required hospitalizations compared to 1 in FMT, which was deemed unrelated to FMT. Infection/HE episodes were similar between groups. Baseline microbial diversity was similar in all tissues between groups. Post‐FMT, duodenal mucosal diversity ( P = 0.01) increased with higher Ruminococcaceae and Bifidobacteriaceae and lower Streptococcaceae and Veillonellaceae. Reduction in Veillonellaceae were noted post‐FMT in sigmoid ( P = 0.04) and stool ( P = 0.05). Duodenal E‐cadherin ( P = 0.03) and defensin alpha 5 ( P = 0.03) increased whereas interleukin‐6 ( P = 0.02) and serum LBP ( P = 0.009) reduced post‐FMT. EncephalApp performance improved post‐FMT only ( P = 0.02). Conclusion: In this phase 1 study, oral FMT capsules are safe and well tolerated in patients with cirrhosis and recurrent HE. FMT was associated with improved duodenal mucosal diversity, dysbiosis, and AMP expression, reduced LBP, and improved EncephalApp performance. Further studies are needed to prove efficacy.